The value of working and preparing efl workshops with Madres Comunitarias Teaching Pre-School Children in the improvement of the english of the Madres Comunitarias Themselves - Raza Alvaro, Andrea (2011)
The present research project is focused on how working and preparing EFL workshops with madres comunitarias teaching pre-school children can be beneficial in the improvement of the English of the madres comunitarias themselves. It is shown and mentioned how this workshop planning and re-creation carry linguistic, methodological and assessment tools when bringing the children closer to English from the earliest ages. The aim of this research project is to explain how working and preparing EFL workshops with madres comunitarias are useful as an alternative way of improving their own English, in order to work this foreign language with the children they are responsible for. As they experience a real and meaningful process of teaching-learning, the madres comunitarias have the opportunity to apply what they experience in every workshop re-creation when working with their little children.